A dominant repressor version of the tomato Sl‐ERF.B3 gene confers ethylene hypersensitivity via feedback regulation of ethylene signaling and response components. (3rd October 2013) - Liu, Mingchun; Pirrello, Julien; Kesari, Ravi; Mila, Isabelle; Roustan, Jean‐Paul; Li, Zhengguo; Latché, Alain; Pech, Jean‐Claude; Bouzayen, Mondher; Regad, Farid
Summary Ethylene Response Factors (ERFs) are downstream components of the ethylene signal transduction pathway, although their role in ethylene‐dependent developmental processes remains poorly understood. As the ethylene‐inducible tomato Sl‐ERF.B3 has been shown previously to display a strong binding affinity to GCC‐box‐containing promoters, its physiological significance was addressed here by a reverse genetics approach. However, classical up‐ and down‐regulation strategies failed to give clear clues to its roles in planta, probably due to functional redundancy among ERF family members. Expression of a dominant repressor ERF.B3‐SRDX version of Sl‐ERF.B3 in the tomato resulted in pleiotropic ethylene responses and vegetative and reproductive growth phenotypes. The dominant repressor etiolated seedlings displayed partial constitutive ethylene response in the absence of ethylene and adult plants exhibited typical ethylene‐related alterations such as leaf epinasty, premature flower senescence and accelerated fruit abscission. The multiple symptoms related to enhanced ethylene sensitivity correlated with the altered expression of ethylene biosynthesis and signaling genes and suggested the involvement of Sl‐ERF.B3 in a feedback mechanism that regulates components of ethylene production and response. Moreover, Sl‐ERF.B3 was shown to modulate the transcription of a set of ERFs and revealed the existence of a complex network interconnecting different ERF genes. Overall, the study indicated that Sl‐ERF.B3 had a critical role in the regulation of multiple genes and identified a number of ERFs among its primary targets, consistent with the pleiotropic phenotypes displayed by the dominant repression lines.